TRANSFUSION PRACTICE, POST-TRANSFUSION COMPLICATIONS AND RISK FACTORS IN SICKLE CELL DISEASE IN SENEGAL, WEST AFRICA. - Moussa Seck; Alioune Badara Senghor; Mossane Loum; Sokhna Aissatou Touré; Blaise Félix Faye; Alioune Badara Diallo; Mohamed Keita; Elimane Seydi Bousso; Sérigne Mourtalla Guèye; Macoura Gadji; Abibatou Sall; Awa Oumar Touré; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Context and Objectives: Blood transfusions (BT) remain a mainstay of therapy for patients with sickle cell disease (SCD), but pose significant clinical challenges. We aim to assess infectious markers, red cell alloimmunization and iron overload secondary to BT in SCD patients.